Traditional Teacher-Oriented Learning to Student-Oriented Learning (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Student-centered /eamlng (nlso cnllod child contorod  /esming) is an approach to oducntlon focusing on tho  needs of the students, mthor than thoso of othors  involved m the l'ducatlonal procoss, such os toachers  and admInistrRlors. T/11s approach hes many  implications for tho dosign of curnculum, course content,  and mreractivif} of courses In terms of curriculum  prachc • the studont has the choice in what they want to  stud\• and ho1, they are going to apply their newfound  knou1edo According to Ernie Stnnger. "Student  leammg -processes are greatly enhanced when they  par11etp,
Keywords: Student-Oriented Learning; Traditional Teacher-Oriented Learning; teacher-centered